Inovasi Pembelajaran Fisika: Integrasi Problem Based Learning dan Simulasi PhET pada Materi Gelombang Bunyi - Flavianus Abrinus Weka Ledjab; Karolina Koli; Maria Vidolina Fatima Tahu; Egidius Dewa (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
This research is motivated by the low learning outcomes of physics students, especially on sound waves material. The purpose of this research is to evaluate the effectiveness of Problem Based Learning (PBL) learning model assisted by PhET simulation in improving students' physics learning outcomes. The research method used was a pseudo experiment with a sample of 28 students of class XI IPA 2 at SMA Negeri 2 Kupang. The data obtained were analyzed by quantitative descriptive method. The results showed that after the application of PBL learning model with PhET simulation there was a significant increase in student learning outcomes. From the results of cognitive tests before treatment (pre-test), there were no students who reached the average percentage level of scores ≥ 75%, with an average score of 19. After the treatment (post-test), 25 out of 28 students were declared complete with an average percentage level of 95 or ≥ 75%. At the stage of observation and observation of affective abilities, 25 students reached an average percentage level ≥ 75%, and 3 students were still below 75%. In the follow-up observation on the psychomotor spec, 26 students reached an average percentage level ≥ 75%, and 2 students were still below 75%. The application of PBL model assisted by PhET simulation is effective in improving students' physics learning outcomes on sound wave material.